Racial/ethnic residential segregation and the availability of opioid and substance use treatment facilities in US counties, 2009-2019 - Michael DiNardi; William L. Swann; Serena Y. Kim (Elsevier, 2022)
Deaths due to synthetic opioids have increased at higher rates for Blacks and Hispanics than for Whites in the last decade. Meanwhile, Blacks and Hispanics experience lower opioid treatment rates and have less availability of medication-assisted treatment (MAT) via office-based buprenorphine in their counties compared to Whites. Racial/ethnic residential segregation is a recognized barrier to equal availability of MAT, but little is known about how such segregation is associated with opioid and substance use treatment availability over time and across Census regions and urban-rural lines. We combined data from the Substance Abuse and Mental Health Services Administration's National Survey of Substance Abuse Treatment Services for 2009, 2014, and 2019 with the 5-year American Community Surveys of 2009, 2014, and 2019 to examine associations between residential segregation indices of dissimilarity and interaction and substance use treatment facilities per 100,000 population, including those providing MAT, in US counties. Estimating county-level two-way fixed effects models and controlling for county-level covariates, we find modest evidence of associations. Despite mostly null findings, an increased likelihood of exposure of Whites to Blacks in a county is associated with fewer substance use treatment facilities per 100,000, particularly those providing MAT via buprenorphine and located in Northeastern and Midwestern counties. Also, a more unequal distribution of Hispanics is associated with fewer facilities per 100,000 providing MAT, and this association is strongest in Southern and Western counties. These associations are driven by recent years (2014-2019) when synthetic opioids became the leading cause of opioid mortality and Blacks and Hispanics began dying at faster rates than Whites. Mixed evidence, however, tempers conclusions for how residential segregation drives racial/ethnic disparities in MAT availability.